Malaysia Blood Bank Android Mobile Application - Lim, Yi Ci (2023)
A person's life can be saved in large part by blood. Blood comes in four different types: A, B, O, and AB. There are a total of eight blood types, with each group having an option to be RhD positive or RhD negative. The only option for medical facilities and governmental agencies to offer a secure blood supply to individuals in need is through blood donations. It might be difficult to find appropriate donors in a short amount of time. Following the introduction of the MCO in Malaysia, the number of blood bags at the National Blood Centre and other blood banks around the country fell by 40%, from 111,328 bags in May 2018 to 67,135 bags (Mac-May 2020). Accordingly, the purpose of this project is to develop a blood bank application that seeks out appropriate blood donors and encourages the public to actively engage in the blood donation campaign. Malaysia Blood Bank Android Mobile Application is developed which include the blood stock status, upcoming donation activity, donation appointment and emergency donation. A User Acceptance Test (UAT) is carried out to find any application flaws. In conclusion, the goal of this study which is find the compatible blood donors and call on the public to actively participate in the blood donation drive had achieved by successfully developed the application.